Perancangan Interior Café Dessert dan Cake Shop di Surabaya - Andereas Pandu Setiawan, Monika Susanto (Intra, 2014)
Dessert is an closing food that having a trend and more developing not only at restaurant or café. This Dessert Café and Cake Shop is a place to enjoy the dish like dessert at all once recreation facilities to take down the saturation where customers can enjoy an education by practicing dessert decoration. This design is all soriety addressed.  This café using counter service system that have a purpose to give fast service and indirect education  by applicating transparency between kitchen area and  food uptake counter. At Cake Shop, product which on sale like cake with whole size where customers can do purchase that served by waiter.                    With concept of Taste in Pleasant, this interior design of dessert café and cake shop be focused in order to customers enjoy dessert with pleasant atmosphere in relaxing at café area along with do practicing decoration appropriate taste and creativity every individual. To edvocating concept, this café design applying modern contemporary style that have an simple and clean character but unique.